Great Christian jurists in the Low Countries - Decock, Wim; Oosterhuis, Janwillem (Law and Christianity, 2021)
What impact has Christianity had on law and policies in the Lowlands from the eleventh century through the end of the twentieth century? Taking the gradual 'secularization' of European legal culture as a framework, this volume explores the lives and times of twenty legal scholars and professionals to study the historical impact of the Christian faith on legal and political life in the Low Countries. The process whereby Christian belief systems gradually lost their impact on the regulation of secular affairs passed through several stages, not in the least the Protestant Reformation, which led to the separation of the Low Countries in a Protestant North and a Catholic South in the first place. The contributions take up general issues such as the relationship between justice and mercy, Christianity and politics as well as more technical topics of state-church law, criminal law and social policy.